Association of Sarcopenia and Urinary Incontinence in Adult Women Aged Less Than 60 years - Zhang F; Li W (International Journal of Women's Health)
Fan Zhang,1,2 Wenjian Li3,4 1Department of Endocrinology, Changzhou Third People’s Hospital, Changzhou, Jiangsu, People’s Republic of China; 2Department of Clinical Nutrition, Changzhou Third People’s Hospital, Changzhou, Jiangsu, People’s Republic of China; 3Department of Urology, Changzhou Third People’s Hospital, Changzhou, Jiangsu, People’s Republic of China; 4Changzhou Clinical College, Xuzhou Medical University, Changzhou, Jiangsu, People’s Republic of ChinaCorrespondence: Wenjian Li, Department of Urology, Changzhou Third People’s Hospital, 300 Lanling North Road, Changzhou, Jiangsu, People’s Republic of China, 213001, Tel +86 0519 82009011, Email bolite@163.comPurpose: This study aimed to explore the association between sarcopenia and urinary incontinence in adult women younger than 60 and provide insights into their pathophysiological mechanisms.Patients and Methods: The study included 4,553 adult female participants aged < 60, utilizing data from the National Health and Nutrition Examination Survey (NHANES) database between 2011 and 2018. The appendicular skeletal muscle mass index (ASMI) was assessed using dual-energy X-ray absorptiometry, and sarcopenia was determined based on the resulting ASMI values (< 0.512). The type of urinary incontinence was evaluated using the Kidney Condition-Urology Questionnaire, which categorized incontinence as stress urinary incontinence, urgency urinary incontinence, or mixed urinary incontinence based on the results of the questionnaire. Multivariate adjustment models were constructed to analyze the relationship between ASMI, sarcopenia, and different types of urinary incontinence. The model incorporated a range of sociodemographic characteristics, lifestyle habits, and medical histories as covariates. Restricted cubic spline model was employed to assess the non-linear dose-response relationship between ASMI and urinary incontinence.Results: The results demonstrated a significant negative correlation between ASMI and the development of urinary incontinence. The risk of developing stress urinary incontinence, urgency urinary incontinence, and mixed urinary incontinence all increased significantly as ASMI decreased. The prevalence of urinary incontinence was significantly higher in patients with sarcopenia than in those without sarcopenia. Subgroup analysis demonstrated that the inverse relationship between ASMI and urinary incontinence persisted across most subgroups.Conclusion: This study identifies a significant inverse association between sarcopenia and urinary incontinence in adult women under 60, emphasizing the role of muscle health in bladder function. These findings provide valuable insights for clinical risk assessment and intervention strategies.Keywords: sarcopenia, urinary incontinence, adult women under 60, appendicular skeletal muscle mass index, NHANES, risk factors